Badania eksperymentalne w zakresie semantyki jzyka naturalnego. Przyczynek do dyskusji nad realnoci psychologiczn hipotez lingwistycznych - Nowak, Tomasz (Postscriptum Polonistyczne, 2020)
The article presents the results of laboratory experiments on several linguistic hypotheses. The experiments were checked for their epistemological control of the psychological reality of the world description that they offer. The article refers to the psycholinguistic experiments that aim to define the explanatory adequacy of the semantic models that simulate the implementation of the representative function of the language. The two themes: philological (linguistic) and cognitive (neurolinguistic and psycholinguistic) are combined in the article.